3D Printed Foods: A Comprehensive Review on Technologies, Nutritional Value, Safety, Consumer Attitude, Regulatory Framework, and Economic and Sustainability Issues. Issue 5 (4th July 2022) - Baiano, Antonietta
ABSTRACT: Three-dimensional printing can be successfully applied in the food sector to fabricate 3D foods with complex geometries, customized texture, and tailored nutritional contents. The concrete application of 3D printing to foods began in the early 2000 s. This work is aimed to provide a comprehensive overview of 3D printed foods. Details and issues concerning ingredients and technologies available for 3D food printing are supplied as well as the discussion of aspects such as nutritional values, safety, acceptability, sustainability, and legal framework of 3D printed foods. The main 3D food applications are based on the extrusion technology and concern natively printable materials such as cereal derivatives and chocolate. However, interesting applications concern alternative ingredients such as proteins and fibres isolated from insects, algae, microorganisms, and agri-food residues. Microbiological contamination and migration of toxic substances from printer elements can occur, but effective cleaning protocols and the use of materials authorized to come into contact with foods guarantee the necessary safety standards. A serious issue concerns acceptability of 3D printed foods, since it is greatly affected by their unusual appearance. From a legal point of view, 3D printed foods should be considered as "novel foods". 3D food printing should be considered an opportunity for the development of new business strategies as well as a way to increase the food supply chain sustainability. The future perspectives of 3D food printing include the combination of 3D food printing and cooking on a single machine and the development of the 4D printing.